Flavonoids Target Human Herpesviruses That Infect the Nervous System: Mechanisms of Action and Therapeutic Insights - Šudomová, Miroslava; Berchová-Bímová, Kateřina; Mazurakova, Alena; Šamec, Dunja; Kubatka, Peter; Hassan, Sherif T S (Viruses, 2022)
Human herpesviruses (HHVs) are large DNA viruses with highly infectious characteristics. HHVs can induce lytic and latent infections in their host, and most of these viruses are neurotropic, with the capacity to generate severe and chronic neurological diseases of the peripheral nervous system (PNS) and central nervous system (CNS). Treatment of HHV infections based on strategies that include natural products-derived drugs is one of the most rapidly developing fields of modern medicine. Therefore, in this paper, we lend insights into the recent advances that have been achieved during the past five years in utilizing flavonoids as promising natural drugs for the treatment of HHVs infections of the nervous system such as alpha-herpesviruses (herpes simplex virus type 1, type 2, and varicella-zoster virus), beta-herpesviruses (human cytomegalovirus), and gamma-herpesviruses (Epstein-Barr virus and Kaposi sarcoma-associated herpesvirus). The neurological complications associated with infections induced by the reviewed herpesviruses are emphasized. Additionally, this work covers all possible mechanisms and pathways by which flavonoids induce promising therapeutic actions against the above-mentioned herpesviruses.
Keywords: flavonoidy; varicella-zoster virus; Flavonoids; Kaposi sarcoma-associated herpesvirus; mechanisms of action; Humans; centrální nervový systém; flavonoids; human cytomegalovirus; lidé; virus Epsteinův-Barrové; herpes simplex virus; neurological diseases; infekce virem Epsteina-Barrové; Epstein-Barr Virus Infections; lidský herpesvirus 1; nervous system; herpetické infekce; Herpesviridae Infections; HSV-2; Herpesvirus 4, Human; virus varicella zoster; Herpesvirus 1, Human; Epstein–Barr virus; Central Nervous System; HSV-1; Herpesvirus 3, Human